3D oxalate-based coordination polymers: Relationship between structure, magnetism and color, studied by high-field ESR spectroscopy. (18th April 2017) - Žilić, D.; Molčanov, K.; Jurić, M.; Habjanič, J.; Rakvin, B.; Krupskaya, Y.; Kataev, V.; Wurmehl, S.; Büchner, B.
Graphical abstract: High field electron spin resonance (HF-ESR) study of three 3D oxalate-based coordination polymers, supported by crystallographic, photoluminescence (PL), elemental (EDX) and X-band ESR analysis. Abstract: The detailed high field electron spin resonance (HF-ESR) study of three 3D oxalate-based coordination polymers with antiferromagnetic ordering below 13 K, supported by crystallographic, photoluminescence (PL), elemental (EDX) and X-band ESR analysis, is presented. Two of the investigated compounds are described by the same chemical formula [Cu(bpy)3 ][Mn2 (C2 O4 )3 ]·H2 On, both exhibit PL but have different colors: green–blue and red–pink (CuMn2-Green and CuMn2-Red, respectively) while [Co(bpy)3 ][Mn2 (C2 O4 )3 ]·H2 On is yellow (CoMn2-Yellow) without PL. Despite different colors of CuMn2-Green and CuMn2-Red, X-ray diffraction, EDX, as well as X-band ESR, could not reveal any difference between these compounds. Therefore, detailed temperature dependent multifrequency HF-ESR experiments were performed. Owing to very high resolution of HF-ESR, two different Mn(II) centers in CuMn2-Green and CoMn2-Yellow compounds could be resolved, while in CuMn2-Red only one Mn(II) center is detected. A possible difference in the ligand coordination of Mn(II) ions in the oxalate-networks of CuMn2-Green and CuMn2-Red, that gives rise to slightly different g -factors, is discussed with respect to the different colors of these compounds.